Public Perceptions of The Government in Handling Covid-19 Pandemic with Covid-Score-10 Approach and Dematel Analytical Network Process (DANP) - Intan Berlianty; Irwan Soejanto (OPSI, 2022)
COVID-19 puts intense pressure on governments to take unprecedented and rapid action around the world in dealing with the COVID-19 pandemic. This research takes steps to determine the public's assessment of government programs to resolve the COVID-19 pandemic. The most likely solution is to use the combined method of the Covid Score and the Analytical Network Process (ANP) in determining how to increase public support for government programs to resolve this pandemic. The results of the data processing provide a significant picture of support for the government by 34% in handling the pandemic. To increase wider community support, it is proposed to apply more stringent rules as shown in the ANP value of 16.2. Research contribution to implementing COVID SCORE 10 with Analytical Network Process (ANP) review for implementation in Covid-19 cases in the sample area